House Prices and Aggregate Consumption: Do they Move Together? Evidence from Singapore - PHANG, Sock Yong (Institutional Knowledge at Singapore Management University, 2004)
Using data from Singapore, we find no evidence that house price increases have produced either wealth or collateral enhancement effects on aggregate consumption. We confirm the presence of liquidity constraints from the asymmetric reaction of consumption to income increases vis-a-vis income declines. When we allow for asymmetric response, anticipated house price increases do not have a positive effect on aggregate consumption: we find that they are considerably more likely to have a modest dampening effect, although this negative result is not statistically significant from zero. Declines in expected house price growth have a larger and marginally significant negative effect on consumption. We conclude that the results of recent studies of OECD countries, which find changes in housing wealth to be positively associated with changes in aggregate consumption, cannot be generalized to the Singapore case.